1989
DOI: 10.1152/jappl.1989.66.2.771
|View full text |Cite
|
Sign up to set email alerts
|

Regionalized adaptations and muscle fiber proliferation in stretch-induced enlargement

Abstract: The relative contribution of increases in fiber area to stretch-induced muscle enlargement was evaluated in the slow tonic fibers of the anterior latissimus dorsi of adult Japanese quails. A weight corresponding to 10% of the bird's body mass was attached to one wing. Thirty days of stretch in 34 birds averaged 171.8 +/- 13.5% increase in muscle mass and 23.5 +/- 0.8% increase in muscle fiber length. The volume density of noncontractile tissue increased in middle and distal regions of stretch-enlarged muscles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 11 publications
4
80
0
Order By: Relevance
“…Birds and small mammals have been studied the most extensively. In general, hypertrophic results from the stretch of chicken and quail wing muscles 5,7,16,18,45,59 have been the same as those found in rabbit 21,30,75 and rat 27 hindlimb muscle stretch models. The functional and hypertrophic outcomes of the stretch model are well documented as described below but the mechanism underlying how stretch induces hypertrophy is not known (although it is likely a mechanoreceptor type of response).…”
Section: Chronic Stretch Modelssupporting
confidence: 61%
See 1 more Smart Citation
“…Birds and small mammals have been studied the most extensively. In general, hypertrophic results from the stretch of chicken and quail wing muscles 5,7,16,18,45,59 have been the same as those found in rabbit 21,30,75 and rat 27 hindlimb muscle stretch models. The functional and hypertrophic outcomes of the stretch model are well documented as described below but the mechanism underlying how stretch induces hypertrophy is not known (although it is likely a mechanoreceptor type of response).…”
Section: Chronic Stretch Modelssupporting
confidence: 61%
“…5,7,16,18,45,59 This unilateral model is advantageous because any systemic alteration (eg, hormonal changes) due to the experimental manipulation are common in the control and stretched muscles, so the effects of the mechanical overload can be distinguished. The use of young chickens is slightly disadvantageous because they continue to grow throughout the experimental period.…”
Section: Chronic Stretch Modelsmentioning
confidence: 99%
“…By 1 week, myofiber cross-sectional area in the weighted wing was not significantly different from contralateral control. These later increases in myofiber size are concurrent with increases in myofibrillar and sarcoplasmic protein content (Laurent et al, 1978;Alway et al, 1989;Matthews et al, 1990). …”
Section: Results and Discussion Hypertrophic Response To Wing-weightingmentioning
confidence: 99%
“…The PAT muscle is flexed with the wing on the birds back at rest, but it is stretched when the wing is extended. In our experimental stretchoverloading model, a tube containing 10 -12% of the bird's body weight was placed over the left humeral-ulnar joint (4). This maintains the joint in extension throughout the period of stretch and induces stretch at the origin of the PAT muscle.…”
Section: Allmentioning
confidence: 99%
“…Previous studies have shown this stretch-overloading protocol results in moderate hypertrophy of the PAT muscles (i.e., 14-day stretch-loading induces ϳ35% and ϳ15% increases in muscle mass of young adult and aged birds, respectively; see Ref. 4). Following 14 days of stretch overload of the left wing, eight young and eight aged birds were killed with an overdose of xylazine.…”
Section: Allmentioning
confidence: 99%